2022
DOI: 10.3389/fpls.2022.829668
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization of Serine/Arginine-Rich Gene Family and Its Genetic Effects on Agronomic Traits of Brassica napus

Abstract: Serine/arginine-rich (SR) proteins are indispensable factors for RNA splicing, and they play important roles in development and abiotic stress responses. However, little information on SR genes in Brassica napus is available. In this study, 59 SR genes were identified and classified into seven subfamilies: SR, SCL, RS2Z, RSZ, RS, SR45, and SC. In each subfamily, the genes showed relatively conserved structures and motifs, but displayed distinct expression patterns in different tissues and under abiotic stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 82 publications
5
8
0
Order By: Relevance
“…The greater number of SNPs in the genomic regions suggested that a lot of variations occurred in BnARIs during the evolution. The SNP density was much higher in the A subgenome than the C subgenome ( Table S10 ) and these results were consistent with the SR and GATA gene families in B. napus [ 45 , 50 ]. In this study, a total of 271 missense mutations could help in the functional differentiation of these BnARI genes.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The greater number of SNPs in the genomic regions suggested that a lot of variations occurred in BnARIs during the evolution. The SNP density was much higher in the A subgenome than the C subgenome ( Table S10 ) and these results were consistent with the SR and GATA gene families in B. napus [ 45 , 50 ]. In this study, a total of 271 missense mutations could help in the functional differentiation of these BnARI genes.…”
Section: Discussionsupporting
confidence: 79%
“…We did not obtain any ortholog against two AtARI genes ( AtARI6 ( At1g63760 ), AtARI4 ( At3g27720 ) which were considered as pseudogenes [ 9 ]). Many studies showed that WGD or segmental duplication play a critical role during the expansion of gene families [ 44 , 45 , 46 ]. We obtained similar results in BnARI genes: all the genes were produced from the WGD or segmental duplication except four genes BnaAnng26970D , BnaAnng26980D , BnaC04g42500D , BnaA03g14710D and BnaC03g50620D , which were produced as a result of tandem duplication events ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that 41 BnaGRFs were generated by WGD or segmental duplication; four BnaGRFs (BnaGRF28, BnaGRF23, BnaGRF28, and BnaGRF23) were a result of dispersed duplication; BnaGRF40, which is separated from BnaGRF39 by only a few genes, originated by proximal duplication; and no BnaGRFs were caused by tandemly duplication (Table 1 and Figure 4). These results indicate that WGD and segmental duplications were the key factors responsible for the expansion of the 14-3-3 gene family, which is consistent with previous studies (Xie et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Cis-regulatory elements play an important role in the regulation of plant gene expression. The cis-acting element and expression pattern analysis showed that 14-3-3s were involved in hormone and abiotic stress responses in plants (Lyu et al, 2021;Xia et al, 2022;Xie et al, 2022). In this study, we analyzed the stress response-related cis-acting elements in the promoters of BnaGRFs.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Plant Science 13 frontiersin.org He et al 10.3389/fpls.2022.983786 account for the differences in the number of CDP family members between B. napus and A. thaliana. In our results, 75.0% of BnCDPs (72 BnCDP genes) were originated from WGD or segmental duplication, which is consistent with the conclusion that WGD and segmental duplication are the main contributors to the expansion of gene families in other researches (Ma et al, 2017;Wu et al, 2018;Xie et al, 2022). Since B. napus was formed by the interspecific hybridization between B. rapa and B. oleracea about 7,500 years ago, both of which had undergone a genome triplication event after divergence from A. thaliana lineage, six homologs for each A. thaliana gene are expected to be present in B. napus (Allender and King, 2010).…”
Section: Discussionsupporting
confidence: 91%